Relationship between psycho- demographic factors and perception of corruption by local government civil servants in Osun State, Nigeria (2011)
Even though global corruption is assuming a worrisome dimension in Nigeria. This study investigated the relationship between psychological and demographic factors in predicting the perception of corruption. The cross-sectional correlational study included 600 Civil servants: 320 males an d 230 females following multi-stage sampling. A 67 item questionnaire was used for data collection Data analysis included Pearson Product Moment Correlation and regression. Results showed that there was significant positive relationship between fraudulent intent (r = 0.671, P<.05), personality (r = 0.631, P<.05), fear of crime (r =0.491, P<.05), need for achievement (r = 0.486, P<.05), and perception of corruption. There was Significant relationship between age of the respondents (r =0.385, P<.05) and perception of corruption. There was no Significant relationship between level of education (r = 0.049, P>.05). socioeconomic status (r = 0.041, P>.05), length of service (r = 0.020, P>.05), and perception of corruption. This highlights the importance of fraudulent intent, personality and age as factors critical to the understanding of an individual's perception of corruption suggesting the need for national re-orientation and mobilization to reawaken positive cognitive appraisal and response to corruption.